Haemoproteus Columbae Infection In A Flock Of Pigeons - Selvaraj, P.; Umesh, C.G.; Preethi, U.; Sumathi, D.; Nambi, A. P.; Prathaban, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Pigeons and doves are affected by a number of economically important diseases and among which hemoparasitic diseases are very significant (Powers, 2002). Haemoproteus spp. are the most commonly occurring avian blood parasite which infect red blood cells (RBCs) of birds especially pigeons and are closely related to the malaria parasites. Pseudolinchia canariensis, a Hippoboscid fly was incriminated as the vector of H. columbae in Columba livia in natural and experimental infections. Many pigeons harbor the organism without showing signs. This paper reports incidence of the haemoprotozoan - Haemoproteus columbae in seven pigeons in a flock of 56 pigeons and its clinical management.